Students' Usage of Smartphones during the Lectures - Alanoglu, Muslim; Karabatak, Songul (Institute of Electrical and Electronics Engineers Inc., 2020)
The current study aims to investigate students' usage of smartphones during the lectures. To achieve this aim, the survey model was used and a survey form was created by researchers to collect data in the study. The study group was selected among the undergraduate students at a state university. The study group determined by the snowball sampling method consists of 577 students in total. The descriptive analysis was used to analyze the collected data. At the end of the study, it was concluded that most of the students use their phones occasionally and to message, research on lecture subject, and connect to social networks. Causing distraction and the ban on use during the lectures also emerged as the reasons for not using their smartphones during the lectures. The most important reason for using the smartphones during the lectures is to research about the lecture subject and to use in emergencies. Also, students gave close answers to each other about the effects of using smartphone on academic performance. In the last part of the study, some suggestions were developed regarding the results obtained. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: smarthphone usage during the lectures; Smartphone usage; undergraduate students